Level of Student Preparedness in Disaster Alert Schools in Bengkulu City in Dealing with Potential Disaster Threats - Alfi, Muhammad; Utami, Anggun Dwi; Cholisa, Keyshe Nur; Putri, Yulia Eka; Utami, Geby Riyanti (Jurnal Pendidikan Geografi Gea, 2024)
Bengkulu City is an area that has a high potential threat of natural disasters. One effort that can be made is to form a Disaster Preparedness School (SSB). The Bengkulu Provincial Government has formed SSB which is a program of the United National Development Program (UNDP). However, when a school has been labeled SSB but the community in the school environment is not ready, of course, it will be a problem and interesting to study. The aim of this research is to look at the preparedness of students at disaster preparedness schools (SSB) in Bengkulu City in facing the threat of disaster. This research method is qualitative, and descriptive in nature. The population in this study were elementary schools, middle schools, and high schools located in the red zone of disaster threat in Bengkulu City. The sample in this study consisted of a sample of the school environment and a sample of respondents (students and teachers). School environment samples were taken using purposive sampling techniques. Sampling considerations are 1) elementary schools, middle schools, and high schools located less than 500 meters from the beach; 2) a topography of 25 meters above sea level; and 3) a slope of 0% -15% from sea level. The samples in this study were SD Negeri 1, SMP Negeri 15, and SMA Negeri 6 Bengkulu City. The sample of respondents were students. The sampling of student and teacher respondents in this study used the Proportionate Stratified Random Sampling technique by taking 10% of the number of students per class in each disaster-prepared school. The sample of student respondents was 187 students and the sample of teacher respondents was 117 people. This research will be carried out for one year—data collection techniques using questionnaires, interviews, and documentation studies. The research results show that the preparedness of students at the disaster preparedness school SDN 1 Kota Bengkulu falls into the ready category with a score of 53.9 or 50.0075. The readiness of students at the disaster preparedness school SMPN 15 Bengkulu City falls into the ready category with a score of 53.57 or 50.0075. The preparedness of students at the SMAN 6 Bengkulu City disaster preparedness school is included in the ready category which is at 71.25 or 75.00.